Protective effects of engineered Lactobacillus johnsonii expressing bovine granulocyte-macrophage colony-stimulating factor on bovine postpartum endometritis - Guo, Jing; Cao, Xu; Li, Zhiqiang; Wang, Caiyu; Zhong, Chengkun; Wang, Simin; Fan, Zhile; Zhao, Jing; Wang, Jun; Fang, Yi; Liu, Hongyu; Ding, He; et al. (Frontiers in Veterinary Science, 2024)
Introduction Postpartum endometritis is a prevalent reproductive disorder in bovines, leading to a prolonged open period, infertility, and other complications. While Lactobacillus strains can mitigate these conditions by reducing uterine inflammation, their effectiveness is limited due to a lack of direct anti microbial action and extended treatment duration. This study aimed to construct a recombinant Lactobacillus johnsonii strain expressing bovine Granulocyte-macrophage colony-stimulating factor (GM-CSF) to evaluate its potential in reducing postpartum uterine inflammation. Methods The recombinant Lactobacillus johnsonii strain was engineered to express bovine GM-CSF and administered to pregnant mice via vaginal perfusion. Postpartum endometritis was induced using E. coli infection, and the protective effects of the engineered strain were assessed. Inflammatory markers (IL-6, IL-1β, TNF-α), myeloperoxidase (MPO) activity, and nitric oxide (NO) concentration were measured. Histological examination was performed to evaluate uterine morphology and pathological damage. Results The recombinant L. johnsonii strain expressing GM-CSF significantly reduced inflammation levels induced by E. coli infection in the uterus. This reduction was evidenced by decreased expression of IL-6, IL-1β, TNF-α, as well as reduced MPO activity and NO concentration. Histological examination revealed improved uterine morphology and reduced pathological damage in mice treated with the recombinant GM-CSF strain. Crucially, the recombinant strain also exerts beneficial effects on bovine endometritis by reducing levels of inflammatory cytokines, suggesting a beneficial effect on clinical bovine endometritis. Conclusion The recombinant Lactobacillus johnsonii expressing GM-CSF demonstrated protective effects against postpartum endometritis in bovines by reducing inflammatory cytokines. The findings indicate the potential clinical application of this engineered strain in preventing postpartum uterine inflammation, offering a novel and effective protective option for related disorders and improving bovine reproductive efficiency.